Implementation Challenges and Effectiveness of the Family Hope Program (PKH) in Reducing Poverty: Evidence from Kabul Village Central Lombok - M. Yakub; Nuli Purwanti (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2023)
This study examines the implementation challenges and effectiveness of Indonesia’s Program Keluarga Harapan (PKH), or Family Hope Program, in reducing poverty at the local level, focusing on Kabul Village in Central Lombok Regency. The research aims to analyze how national social assistance policies are translated into local practices and how these processes affect the well-being of poor households. Employing a qualitative descriptive approach, data were collected through in-depth interviews, direct observation, and document analysis involving program facilitators, local government officials, and beneficiary families. The findings indicate that the PKH has positively contributed to short-term poverty alleviation by improving household access to education, healthcare, and social protection services. However, its overall effectiveness remains limited by inaccurate targeting, inconsistent monitoring, and a lack of empowerment programs following cash assistance distribution. The study argues that sustainable poverty reduction requires the transformation of PKH from a welfare-oriented transfer scheme into an empowerment-based initiative supported by strong inter-agency coordination, accurate data systems, and local administrative capacity. This research contributes to the broader discourse on social policy implementation and local governance by demonstrating the need for adaptive policy mechanisms that align national welfare objectives with local socio-economic realities.